Taxonomic review of the species of Andrenosoma (Diptera: Asilidae) in Spain and description of a new species - García, Marta; Pérez, Guillermo; Portillo, Manuel (Zootaxa, 2017)
Currently, only two species of Andrenosoma are listed from Spain: A. albibarbe (Meigen) and A. atrum (Linnaeus). Here we add three additional species to Spanish list. A. bayardi Séguy, A. cyrtoxys Séguy and A. biacuminatum n.sp. The new species is described and identification key to the Andrenosoma species of Spain is given, as well as new information on the biology and distribution of the genus in Spain.